2020
DOI: 10.3390/foods9060687
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Supplementation of Anthocyanins on Obesity-Associated Comorbidities: A Concise Review

Abstract: Anthocyanins are water-soluble plant pigments, and based on their chemical structure (nature, position, and the number of sugar moieties attached; the number of hydroxyl groups; acylation of sugars with acids) about 635 different anthocyanins have been identified and reported from plants. Cyanidin, peonidin, pelargonidin, petunidin, and malvidin are the commonly found anthocyanidins (aglycon forms of anthocyanins) in edible plants out of almost 25 anthocyanidins that are identified (based on the position of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 83 publications
1
40
0
1
Order By: Relevance
“…Several in vitro and in vivo studies confirmed that ACN-rich food consumption prevents obesity-related consequences such as diabetes, inflammation and oxidative stress. ACN supplementation favorably alters genes involved in glucose, FA and lipid metabolism, immune and inflammatory system, antioxidant defense, and the antiangiogenic system [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several in vitro and in vivo studies confirmed that ACN-rich food consumption prevents obesity-related consequences such as diabetes, inflammation and oxidative stress. ACN supplementation favorably alters genes involved in glucose, FA and lipid metabolism, immune and inflammatory system, antioxidant defense, and the antiangiogenic system [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanins, the pigmented flavonoids, have anti-inflammatory, anti-diabetic and anti-obesity activities. In animals, anthocyanin supplementation reduced body weight gain, visceral fat and lipid levels, and alleviated leptin resistance [ 149 ]. Purified cyanidin-3-glucoside was found to induce thermogenesis by increasing mitochondrial UCP1 expression and activating AMPK phosphorylation [ 149 ].…”
Section: Other Plants and Phytochemicals With Anti-obesity Activitmentioning
confidence: 99%
“…Vital et al found that cyanidin and delphinidin glucosides are potent inductors of insulin secretion [ 9 ]. It was observed that the consumption of anthocyanidin-rich extracts prevents obesity in healthy subjects, and helps to reduce the body weight of obese subjects [ 10 ]. Silveira et al report that the daily intake of red orange juice (cyanidin glucosides as major active factors) [ 21 ] leads to an increase in serum antioxidant activity and reduction in the levels of C-reactive protein as well as total- and low-density lipoprotein cholesterol [ 22 ].…”
Section: Introductionmentioning
confidence: 99%